2019
DOI: 10.1136/bmjopen-2019-030206
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with hypertension among adults in Nepal as per the Joint National Committee 7 and 2017 American College of Cardiology/American Heart Association hypertension guidelines: a cross-sectional analysis of the demographic and health survey 2016

Abstract: ObjectivesThis study investigated the determinants of hypertension in Nepal according to both the Joint National Committee 7 (JNC7) and the American College of Cardiology/American Heart Association (2017 ACC/AHA) guidelines.DesignCross-sectional study.SettingThis study used data collected from the 2016 Nepal Demographic and Health Survey data.Participants13 393 weighted adults aged ≥18 years enrolled by a stratified cluster sampling strategy were included in our analysis.Primary and secondary outcome measuresT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
4
9
1
Order By: Relevance
“…From the random effects model estimate, the pooled odds of developing hypertension among males were 29% higher than females. This finding was similar with the studies conducted in Nepal, Varanasi India, Burkina Faso, Debrecen city of Hungary, and a meta-analysis study from Vietnam [ 62 , 69 , 77 80 ], whereas it is not similar to a study conducted at Uganda [ 81 ]. The possible reason might be males were more vulnerable to behavioral risk factors for hypertension.…”
Section: Discussionsupporting
confidence: 88%
“…From the random effects model estimate, the pooled odds of developing hypertension among males were 29% higher than females. This finding was similar with the studies conducted in Nepal, Varanasi India, Burkina Faso, Debrecen city of Hungary, and a meta-analysis study from Vietnam [ 62 , 69 , 77 80 ], whereas it is not similar to a study conducted at Uganda [ 81 ]. The possible reason might be males were more vulnerable to behavioral risk factors for hypertension.…”
Section: Discussionsupporting
confidence: 88%
“…The independent variables included in the study were selected based on previous literature reporting the risk of developing hypertension in populations of LMICs. 18,19,29,30,[33][34][35][36][37] The household-level factors included: administrative division (Barisal, Chittagong, Dhaka, Khulna, Mymensingh, Rajshahi, Rangpur, Sylhet), place of residence (urban, rural), and wealth status (poor, middle, rich). Socioeconomic and individual-level factors were: sex of participants (male, female), age of participants in years (18-20, 21-24, 25-30, 31-34), education level (no education, primary, secondary, higher), and occupational status (not working, working).…”
Section: Independent Variablesmentioning
confidence: 99%
“…From the random effects model estimate, the pooled odds of developing hypertension among males were 29% higher than females. This finding was similar with the studies conducted in Nepal, Varanasi India, Burkina Faso, Debrecen city of Hungary, and a meta-analysis study from Vietnam [62,69,[77][78][79][80], whereas it is not similar to a study conducted at Uganda [81]. The possible reason might be males were more vulnerable to behavioral risk factors for hypertension.…”
Section: Discussionsupporting
confidence: 87%
“…The pooled effect of age greater than 35 years was 3.6 times higher than age less than 35 years to develop hypertension, which is similar to the community-based studies conducted in Uganda, Nepal, Benin, Varanasi city India, and another city of New Delhi, India [79][80][81][82][83]. As well, from meta-regression analysis showed that mean age and hypertension had a direct linear relationship.…”
Section: Discussionsupporting
confidence: 78%